Accelerated Biodegradation of Waste Polyethylene Terephthalate (PET) Fiber by Recombinant Hydrophobin HGFI Fused with Ideonella sakaiensis PETase - Puspitasari, Nathania; Liu, Chia Tzu; Lee, Cheng Kang (Indonesian Journal of Chemistry, 2025)
Nowadays, an efficient and environmentally friendly polyethylene terephthalate (PET) recycling method has gained greater attention, enabling a circular economy for polyesters. Since PET is a hydrophobic polymer, the enzyme's binding affinity to PET becomes a significant issue. Herein, the first strategy is introduced to enhance PET fiber hydrolysis by genetically fusing hydrolyzing enzymes such as cutinase and PETase to protein hydrophobin HGFI. HGFI, a surface-active protein from Grifola frondosa, was used to improve the rate of enzyme hydrolysis. Furthermore, cellulose binding domains (CBD) were employed as a solubility enhancer tag of PETase fusion due to the insoluble characteristics of HGFI and PETase. The fusion proteins (CBD-HGFI-PETase and HGFI-Cut_2) were constructed with a flexible linker, expressed in Escherichia coli, and then purified by chromatography. PETase fusion exhibited 2.5-fold higher concentrations of monomer products released than that of cutinase fusion after 5 days of hydrolysis. According to the results, the fusion of HGFI to PETase showed excellent performance for enhancing the binding affinity of the enzyme on PET fiber substrate due to the increasing number of self-assembled hydrophobin interactions that modified the PET surface to be more hydrophilic. Therefore, this study indicates that the construction of CBD-HGFI-PETase enzyme fusion could be used as a novel method for efficiently accelerating PET biodegradation.